1986
DOI: 10.1017/s0022172400063592
|View full text |Cite
|
Sign up to set email alerts
|

Speciation, serotyping, antimicrobial sensitivity and plasmid content of Proteeae from the environment of calf-rearing units in South West England

Abstract: rettgeri. A wide range of serotypes was found, many having been previously reported from nosocomial isolates. A total of 15 % of isolates carried plasmids; six pairs of isolates were identified which had identical serotypes but different patterns of plasmid carriage. The antimicrobial sensitivity of the isolates was generally similar to isolates of Proteeae from humans. Although no truly aminoglycosideresistant isolates were found, some isolates of Prov. stuartii and Prov. rettgeri had MIC's higher than the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…As few as 10 % of the strains tested contained plasmid DNA. A similar rate (15 %) has been reported for Proteae isolated from animal sources although that study did not include Proteus penneri (11). In our study only ampiciltin and tetracycline resistance markers could be transferred to Escherichia coli.…”
Section: Methodssupporting
confidence: 84%
“…As few as 10 % of the strains tested contained plasmid DNA. A similar rate (15 %) has been reported for Proteae isolated from animal sources although that study did not include Proteus penneri (11). In our study only ampiciltin and tetracycline resistance markers could be transferred to Escherichia coli.…”
Section: Methodssupporting
confidence: 84%
“…Hawkey et al [56] revealed that P. vulgaris (including the strains currently numbered among genomospecies) as well as P. mirabilis species were, respectively, the first and the third species among the tribe Proteeae most commonly isolated from beddings contaminated with feces and urine in two calf farms in South West England. The authors concluded that the high similarity of the O-serotype profile of isolated strains (e.g., serotypes O23 and O30) to those reported for human infections (Table 2) suggests that food animals may be a source of Proteeae strains carried in human gut.…”
Section: Proteus Spp In Animals—adverse and Friendlymentioning
confidence: 99%
“…Serotyping, bacteriocin and bacteriophage typing, numerical analysis of electrophoretic protein patterns, plasmids, and antibiotic resistance pattern determination have been used for typing some species and have been applied to epidemiological investigations with variable efficiency (2,7,12,17,20,25). In more recent years, molecular typing by ribosomal DNA (rDNA) fingerprints (ribotyping), based on restriction fragment length polymorphism in the chromosomal DNA containing rRNA genes (9,18), has been applied for the epidemiological study of P. stuartii clinical isolates (19).…”
mentioning
confidence: 99%